PENGEMBANGAN MEDIA MONOPOLI BERBASIS KONTEKSTUAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS VIII SMPN 7 MUARO JAMBI - Asep Riyadi; Heri Usmanto; Yuslistia Opeska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the lack of engaging learning media in the subject of Pancasila Education in class VIII at SMPN 7 Muaro Jambi. Learning that is still dominated by textbooks causes students to be less active, easily bored, and experience difficulties in understanding the material on cultural preservation in their region. Therefore, innovative, interesting, and student-characteristic-based learning media are needed. This study aims to determine the development process as well as the validity and practicality level of contextual-based monopoly learning media in Pancasila Education for class VIII students at SMPN 7 Muaro Jambi. This research employed the Research and Development (R&D) method using the Suparman MPI model, which consists of six stages: instructional analysis, identification of student characteristics, formulation of instructional objectives, development of instructional strategies, development of instructional materials, and formative evaluation. The research subjects were class VIII students of SMPN 7 Muaro Jambi. Data collection techniques used validation questionnaires from material experts, media experts, and language experts, as well as practicality questionnaires for teachers and students using a Likert scale. The results of the study showed that the contextual-based monopoly media was categorized as very valid and very practical. The material expert validation obtained a score of 4.8, media expert 4.2, and language expert 4.2, all categorized as very valid. The practicality test conducted by students obtained a score of 4.4 and by the teacher 4.2, categorized as very practical. Therefore, the contextual-based monopoly learning media is feasible to be used in Pancasila Education learning on the topic of cultural preservation in their region.